Solid electrolyte, and electrode mixture, solid electrolyte layer, and solid battery using the same

A solid electrolyte with controlled crystallite size of lithium halide in the argyrodite structure addresses conductivity and hydrogen sulfide issues, enhancing performance in solid-state batteries.

JP7601783B2Active Publication Date: 2024-12-17MITSUI MINING & SMELTING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021553457
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-29
Filing Date
2020-10-20
Publication Date
2024-12-17
Estimated Expiration
2040-10-20

AI Technical Summary

Technical Problem

Conventional sulfide solid electrolytes with an argyrodite crystal structure containing lithium halide as a different phase suffer from adverse effects on lithium ion conductivity and generate hydrogen sulfide due to moisture interaction.

Method used

A solid electrolyte comprising a compound with an argyrodite crystal structure, containing lithium halide as a specific phase with controlled crystallite size of 25 nm or more, suppresses hydrogen sulfide generation and enhances lithium ion conductivity.

Benefits of technology

The electrolyte effectively suppresses hydrogen sulfide generation while maintaining high lithium ion conductivity by controlling the crystallite size of lithium halide, ensuring improved performance in solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601783000001
    Figure 0007601783000001
Patent Text Reader

Abstract

A solid electrolyte according to the present invention contains: a compound A which contains a crystal phase having an argyrodite crystal structure, and which is represented by LiaPSbXc (wherein X represents at least one halogen element; a represents a number from 3.0 to 6.0; b represents a number from 3.5 to 4.8; and c represents a number from 0.1 to 3.0); and a compound B which is represented by LiX (wherein X is as defined above). The compound B has a crystallite size of 25 nm or more. It is preferable that this solid electrolyte has a BET specific surface area of 14.0 m2 / g or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid electrolyte, and an electrode mixture, a solid electrolyte layer, and a solid-state battery using the same. [Background technology]

[0002] In recent years, solid electrolytes have been attracting attention as an alternative to the electrolytes used in many liquid batteries. Solid-state batteries using such solid electrolytes are expected to be put to practical use as batteries that are safer than liquid batteries that use flammable organic solvents, and also have a high energy density.

[0003] As a conventional technique related to solid electrolytes, for example, the technique described in Patent Document 1 is known. The document describes a sulfide solid electrolyte, which is one of the solid electrolytes used in lithium ion batteries. Various crystal structures of sulfide solid electrolytes are known, one of which is the argyrodite crystal structure. The document describes that a solid electrolyte containing a compound containing a crystalline phase having an argyrodite crystal structure does not contain lithium halide, or if it does contain lithium halide, it is desirable that the amount of lithium halide is small. The document also describes that a sulfide solid electrolyte has a problem in that it may react with moisture in the air to generate hydrogen sulfide. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] US2019 / 305371A1 Summary of the Invention

[0005] It has been believed that lithium halide contained as a heterophase in a solid electrolyte containing a compound containing a crystal phase having an argyrodite-type crystal structure adversely affects the lithium ion conductivity of the solid electrolyte. However, no study has been conducted on how lithium halide affects the generation of hydrogen sulfide from the solid electrolyte. Therefore, an object of the present invention is to provide a solid electrolyte capable of suppressing the generation of hydrogen sulfide.

[0006] As a result of intensive research by the present inventors to solve the above problems, it was unexpectedly discovered that the presence of a lithium halide having a specific structure in a solid electrolyte suppresses the generation of hydrogen sulfide from the solid electrolyte. The present invention is based on this discovery, and provides a method for producing a lithium halide-containing solid electrolyte comprising the steps of: a P.S. b X c (X is at least one halogen element; a is a number of 3.0 or more and 6.0 or less; b is a number of 3.5 or more and 4.8 or less; and c is a number of 0.1 or more and 3.0 or less), and a compound B represented by LiX (wherein X is as defined above), The above-mentioned problems are solved by providing a solid electrolyte in which the crystallite size of the compound B is 25 nm or more. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The present invention will be described below based on its preferred embodiments. a P.S. b X c (X is at least one halogen element; a is a number of 3.0 or more and 6.0 or less; b is a number of 3.5 or more and 4.8 or less; and c is a number of 0.1 or more and 3.0 or less). Compound A is solid at room temperature (25° C.) and has lithium ion conductivity. The solid electrolyte of the present invention contains, in addition to compound A, compound B represented by LiX (wherein X is defined as above).

[0008] Compound A in the present invention is a crystalline material containing a crystal phase having an argyrodite-type crystal structure. However, compound A may contain a glass component, i.e., an amorphous component. Compound A "containing a crystal phase having an argyrodite-type crystal structure" means that compound A needs to contain at least a crystal phase having an argyrodite-type crystal structure, and may contain a crystal phase (also referred to as a "heterogeneous phase") different from the crystal phase having the argyrodite-type crystal structure. Of course, it is not necessary for compound A to contain the heterogeneous phase. An example of a compound constituting the heterogeneous phase is Li3PS4.

[0009] In compound A, the ratio of the crystal phase having an argyrodite crystal structure to all crystal phases constituting compound A may be, for example, 10% by mass or more, 20% by mass or more, or 50% by mass or more. In particular, it is preferable that compound A contains a crystal phase having an argyrodite crystal structure as a main phase. Here, the "main phase" refers to the phase that accounts for the largest proportion of all the crystalline phases constituting the solid electrolyte of the present invention. Therefore, the content of compound A is preferably, for example, 60% by mass or more, more preferably 70% by mass or more, 80% by mass or more, or even more preferably 90% by mass or more, based on the total amount of all the crystalline phases constituting the solid electrolyte of the present invention. On the other hand, the term "heterogeneous phase" refers to a phase that is smaller in proportion than the above-mentioned main phase with respect to the total amount of all crystalline phases constituting the solid electrolyte of the present invention. Therefore, the content of compound B is preferably, for example, 40 mass% or less with respect to all crystalline phases constituting the solid electrolyte of the present invention, and more preferably 30 mass%, 20 mass% or less, or 10 mass% or less. The proportion of the crystalline phase can be determined by calculating the content ratio by, for example, X-ray diffraction measurement.

[0010] Having a crystal phase with an argyrodite-type crystal structure means having a crystal phase possessed by a group of compounds derived from a mineral represented by the chemical formula: Ag8GeS6. From the viewpoint of improving lithium ion conductivity, it is particularly preferable that compound A containing a crystal phase with an argyrodite-type crystal structure has a crystal structure belonging to a cubic system.

[0011] Whether or not the solid electrolyte of the present invention contains a compound containing a crystal phase having an argyrodite crystal structure can be confirmed by, for example, XRD measurement. That is, in an X-ray diffraction pattern measured by an X-ray diffractometer using CuKα1 radiation, the crystal phase of the argyrodite crystal structure has characteristic peaks at 2θ=15.34°±1.00°, 17.74°±1.00°, 25.19°±1.00°, 29.62°±1.00°, 30.97°±1.00°, 44.37°±1.00°, 47.22°±1.00°, and 51.70°±1.00°. Furthermore, for example, characteristic peaks are present at 2θ=54.26°±1.00°, 58.35°±1.00°, 60.72°±1.00°, 61.50°±1.00°, 70.46°±1.00°, and 72.61°±1.00°. In this specification, the term "peak" means the apex of a peak. It is preferable that the peaks do not overlap with other peaks and exist independently.

[0012] In the solid electrolyte of the present invention, the crystal phase of the argyrodite-type crystal structure constituting compound A preferably constitutes a major phase with respect to all crystal phases. On the other hand, compound B preferably constitutes a minor phase in the solid electrolyte of the present invention, and is a substance of a different phase from the crystal phase of the argyrodite-type crystal structure. Therefore, when X-ray diffraction measurement is performed on the solid electrolyte of the present invention, at least the crystal phase of the argyrodite-type crystal structure and the crystal phase derived from compound B are observed.

[0013] In the solid electrolyte of the present invention, it is preferable that the crystallite size of compound B is controlled. As a result, the solid electrolyte of the present invention is one in which generation of hydrogen sulfide is suppressed. The present inventors believe that the reason for this is as follows.

[0014] As described above, the solid electrolyte of the present invention contains compound A. When compound A is produced, compound B may inevitably coexist in the product. In general, compound B is considered to be a compound that has strong hygroscopicity and can adsorb moisture in the air. Focusing on this point, the present inventors further investigated and found that when compound B having a crystallite size larger than a specific value exists as a different phase in compound A, the hygroscopic effect of compound B becomes even stronger. As a result, the reaction between compound A and moisture in the air is less likely to occur, and the solid electrolyte of the present invention is one in which the generation of hydrogen sulfide is suppressed.

[0015] From the viewpoint of making the above-mentioned advantageous effects more remarkable, in the solid electrolyte of the present invention, the crystallite size of compound B is preferably 25 nm or more, more preferably 26 nm or more, and even more preferably 27 nm or more.

[0016] In the solid electrolyte of the present invention, it is possible to improve the lithium ion conductivity by controlling the crystallite size of compound B. The present inventor believes that the reason is as follows. From the viewpoint of improving the lithium ion conductivity of the solid electrolyte, it is desirable that the amount of compound B is as small as possible, and ideally, it is not present at all. However, in the currently mainstream manufacturing method of compound A, it is not easy to prevent compound B from being present in the product. Therefore, the present inventor has studied various means for improving the lithium ion conductivity even when compound B coexists as a different phase with compound A containing a crystal phase having an argyrodite crystal structure. As a result, it has been found that by controlling the crystallite size of compound B, which is a different phase, to a small value, the conduction path of lithium ions in the solid electrolyte is not hindered, and the lithium ion conductivity of the solid electrolyte is improved.

[0017] From the viewpoint of making the above-mentioned advantageous effects more remarkable, in the solid electrolyte of the present invention, the crystallite size of compound B is preferably 70 nm or less, more preferably less than 68 nm, and even more preferably 67 nm or less.

[0018] The crystallite size of the compound B contained in the solid electrolyte of the present invention can be determined by X-ray diffraction measurement. A specific method will be described in detail in the examples described later.

[0019] The solid electrolyte of the present invention exhibits a high lithium ion conductivity of preferably 4.0 mS / cm or more, more preferably 4.2 mS / cm or more, and even more preferably 4.5 mS / cm or more at room temperature (25° C.) by controlling the crystallite size of the compound B contained therein. The lithium ion conductivity of the solid electrolyte can be measured by the method described in the Examples below.

[0020] The compound B contained as a heterogeneous phase in the solid electrolyte of the present invention is represented by LiX as described above. X represents at least one halogen element. Examples of X include fluorine, chlorine, bromine, and iodine. When there is one type of X, the compound B includes LiF, LiCl, LiBr, LiI, and the like. When there are two types of X, the compound B is LiX 1 y X 2 z It is expressed as X 1 and X 2 Each represents a different halogen element. Also, y and z represent numbers greater than 0 that satisfy y+z=1. X 1 and X 2 For example, the combination of Cl and Br (i.e., LiCl y Br z ), a combination of Cl and I, and a combination of Br and I. When X is three types, compound B is LiX 1 y X 2 z X 3 v It is expressed as X 1, X 2 and X 3 Each of y, z, and v represents a number greater than 0 that satisfies y+z+v=1. 1 and X 2 and X 3 An example of the combination is a combination of Cl, Br and I. The solid electrolyte of the present invention may contain only one type of the above-mentioned compound B, or may contain two or more types of compound B. When the solid electrolyte of the present invention contains only one type of compound B, it is preferable that the crystallite size of the compound B satisfies the above-mentioned range. On the other hand, when the solid electrolyte of the present invention contains two or more types of compound B, it is preferable that the crystallite size of at least one type of compound B satisfies the above-mentioned range, and it is more preferable that the crystallite sizes of all compounds B satisfy the above-mentioned range.

[0021] As described above, the compound A contained in the solid electrolyte of the present invention is Li a P.S. b X c Here, "compound A is Li a P.S. b X c "represented by" means that compound A is Li a P.S. b X c In this composition formula, a, which indicates the molar ratio of lithium (Li), is preferably, for example, a number between 3.0 and 6.0, more preferably a number between 3.2 and 5.8, and even more preferably a number between 3.4 and 5.4. Note that a may be less than 5.4. In the composition formula, b, which indicates the molar ratio of sulfur (S), is preferably, for example, a number from 3.5 to 4.8, more preferably from 3.8 to 4.6, and even more preferably from 4.0 to 4.4. Note that b may be less than 4.4. Furthermore, in the composition formula, c is preferably, for example, a number of 0.1 or more and 3.0 or less, more preferably a number of 0.2 or more and 2.5 or less, and even more preferably a number of 0.4 or more and 2.0 or less. Compound A in which a, b, and c are within this range has sufficiently high lithium ion conductivity. In the composition formula, X represents at least one halogen element. When X is one type, compound A is Li a P.S. b F c , Li a P.S. b Cl c , Li a P.S. b Br c and Li a P.S. b I c When there are two types of X, compound A is Li a P.S. b X 1 y X 2 z It is expressed as X 1 and X 2 Each represents a different halogen element. Also, y and z represent numbers greater than 0 that satisfy c=y+z. X 1 and X 2 Examples of the combination of X include a combination of Cl and Br, a combination of Cl and I, and a combination of Br and I. When X is three types, compound A is Li a P.S. b X 1 y X 2 z X 3 v It is expressed as X 1 , X 2 and X 3 Each represents a halogen element that is different from the others. Also, y, z, and v represent numbers greater than 0 that satisfy c=y+z+v. X 1 and X 2 and X 3An example of the combination is a combination of Cl, Br and I. The solid electrolyte of the present invention may contain only one type of the above-mentioned compound A, or may contain two or more types of compound A.

[0022] In the present invention, the amount of Li a P.S. b X c Compound A obtained in such a manner may contain elements other than lithium (Li), phosphorus (P), sulfur (S) and halogen (X). For example, it may be possible to replace a part of the lithium (Li) element with another alkali metal element, to replace a part of the phosphorus (P) element with another pnictogen element, or to replace a part of the sulfur (S) element with another chalcogen element.

[0023] In the present invention, in addition to controlling the crystallite size of compound B, it is also preferable to control the crystallite size of compound A. This allows the solid electrolyte of the present invention to have a further improved lithium ion conductivity. From the viewpoint of making this advantageous effect more prominent, in the solid electrolyte of the present invention, the crystallite size of compound A is preferably, for example, 50 nm or more, more preferably 100 nm or more, and particularly preferably 300 nm or more. On the other hand, the crystallite size of compound A may be, for example, 800 nm or less, 600 nm or less, or 400 nm or less. By having the crystallite size of compound A within the above range, the lithium ion conductivity of the solid electrolyte of the present invention can be sufficiently increased.

[0024] When the solid electrolyte of the present invention contains only one type of compound A, it is preferable that the crystallite size of the compound A satisfies the above-mentioned range. On the other hand, when the solid electrolyte of the present invention contains two or more types of compound A, it is preferable that the crystallite sizes of all of the compounds A satisfy the above-mentioned range.

[0025] The crystallite size of the compound A contained in the solid electrolyte of the present invention can be determined by X-ray diffraction measurement. A specific method will be described in detail in the examples described later.

[0026] The solid electrolyte of the present invention may contain, for example, impurities in addition to compound A and compound B. From the viewpoint of low influence on performance, the content of the impurities can be, for example, less than 5 mol%, preferably less than 3 mol%, and particularly preferably less than 1 mol%.

[0027] From the viewpoint of further suppressing the generation of hydrogen sulfide, the solid electrolyte of the present invention has a BET specific surface area of ​​14.0 m 2 / g or less, and 13.5m 2 / g or less, and more preferably 13.0m 2 From the viewpoint of suppressing the generation of hydrogen sulfide, the smaller the BET specific surface area, the more preferable. 2 / g or more, especially 2.0m 2 / g or more, especially 2.5m 2 / g, it is possible to sufficiently suppress the generation of hydrogen sulfide. The BET specific surface area in this range can be achieved, for example, by controlling the particle size of the solid electrolyte. The method for measuring the BET specific surface area will be described in detail in the Examples below.

[0028] The solid electrolyte of the present invention is composed of a powder as an aggregate of particles. The particle size of the solid electrolyte of the present invention is measured by a volume cumulative particle size distribution measurement method using a laser diffraction scattering type particle size distribution measurement method. 50 The volume cumulative particle diameter D is preferably 0.7 μm or more, more preferably 0.75 μm or more, and particularly preferably 0.79 μm or more. 50 The volume cumulative particle diameter D of the solid electrolyte of the present invention is preferably 10.0 μm or less, more preferably 8.5 μm or less, and particularly preferably 7.0 μm or less. 50By having the lower limit, it is possible to effectively suppress the generation of hydrogen sulfide from the solid electrolyte. In addition, it is possible to suppress an increase in the surface area of ​​the entire powder of the solid electrolyte, and to suppress the occurrence of problems such as an increase in resistance and difficulty in mixing with the active material. On the other hand, the volume cumulative particle diameter D of the solid electrolyte of the present invention is 50 When the upper limit is satisfied, the contact points and contact area between the solid electrolytes are increased, and the lithium ion conductivity can be effectively improved. In addition, when the solid electrolyte of the present invention is used in combination with another solid electrolyte, the solid electrolyte of the present invention is easily inserted into the gaps of the other solid electrolyte.

[0029] The above mentioned D 50 In relation to the above, the solid electrolyte of the present invention has a volume cumulative particle size D at 10% by volume of cumulative volume measured by a laser diffraction scattering type particle size distribution measurement method. 10 is preferably 5.0 μm or less, more preferably 3.5 μm or less, and particularly preferably 2.0 μm or less. 10 For example, it is preferably 0.2 μm or more, more preferably 0.3 μm or more, and particularly preferably 0.4 μm or more. The solid electrolyte of the present invention has a volume cumulative particle size D at 95% cumulative volume by a laser diffraction / scattering particle size distribution measurement method. 95 is preferably 40 μm or less, more preferably 30 μm or less, and particularly preferably 20 μm or less. 95 For example, it is preferably 1.5 μm or more, more preferably 2.0 μm or more, and particularly preferably 2.5 μm or more. The volume cumulative particle size D 10 and D. 95 By setting the temperature within the above-mentioned range, it is possible to more effectively suppress the generation of hydrogen sulfide from the solid electrolyte, and the contact points and contact area between the solid electrolytes are increased, which makes it possible to more effectively improve the lithium ion conductivity, which is preferable.

[0030] The solid electrolyte of the present invention can be preferably manufactured by the method described below. A lithium source compound, a phosphorus source compound, a sulfur source compound, and a halogen source compound are used as raw materials. For example, lithium sulfide (Li2S) can be used as the lithium source compound. For example, diphosphorus pentasulfide (P2S5) can be used as the phosphorus source compound. When the lithium source compound and / or the phosphorus source compound is a sulfide, the sulfide can be used as the sulfur source compound. For the halogen source compound, compound B (LiX) can be used. These raw materials are mixed so that the lithium element, the phosphorus element, the sulfur element, and the halogen element are in a predetermined molar ratio. Then, the mixed raw materials are fired in an inert atmosphere or in an atmosphere containing hydrogen sulfide gas, thereby obtaining Li. a P.S. b A c A compound containing a crystal phase represented by the formula (I) and having an argyrodite crystal structure is obtained. The atmosphere containing hydrogen sulfide gas may be 100% hydrogen sulfide gas, or may be a mixed gas of hydrogen sulfide gas and an inert gas such as argon. The firing temperature is preferably, for example, 350° C. or higher and 550° C. or lower. The holding time at this temperature is preferably, for example, 0.5 hours or higher and 20 hours or lower.

[0031] A solid electrolyte containing compound A is obtained by the above-mentioned method. A small amount of compound B coexists in this solid electrolyte. By controlling the crystallite size of compound B, the generation of hydrogen sulfide from the solid electrolyte can be suppressed. As a result of the study by the present inventors, it was found that it is advantageous to subject the solid electrolyte to a predetermined pulverization treatment in order to control the crystallite size of compound B.

[0032] The pulverization process can be performed by a wet or dry method. Various media mills can be used for the pulverization process. As the media mill, a ball mill, a bead mill, a paint shaker, a homogenizer, etc. can be used. As the dispersion media used in the media mill, balls and beads made of various ceramics including alumina and zirconia are used. The diameter of the dispersion media can be, for example, 0.1 mm or more and 50 mm or less.

[0033] When the grinding process is performed by a wet method, it is preferable to use an organic solvent as a dispersion medium, since it can suppress the generation of hydrogen sulfide caused by the reaction between the solid electrolyte and water. Examples of the organic solvent include aromatic organic solvents such as toluene, xylene, benzene, and solvent naphtha, and aliphatic organic solvents such as heptane, decane, normal hexane, cyclohexane, and mineral spirits. These organic solvents can be used alone or in combination of two or more.

[0034] The organic solvent and the solid electrolyte are mixed to form a slurry, and the slurry is subjected to wet pulverization. The concentration of the solid electrolyte contained in the slurry is preferably set to, for example, 5% by mass or more and 50% by mass or less, in order to successfully obtain a solid electrolyte with high lithium ion conductivity. In the wet pulverization using a media mill, the ratio of the dispersion medium to the slurry is preferably 5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the slurry, in order to easily obtain a solid electrolyte with high lithium ion conductivity. The dispersion time by the media mill is generally preferably set to 0.5 hours or more and 60 hours or less, in order to easily obtain a solid electrolyte with high lithium ion conductivity.

[0035] When wet grinding is performed, the volume cumulative particle size D of the solid electrolyte after wet grinding is 50It is preferable to adjust the degree of pulverization so that the volume cumulative particle size D of the solid electrolyte after wet pulverization is preferably 0.45 μm or more, more preferably 0.50 μm or more, and even more preferably 0.55 μm or more, from the viewpoint of sufficiently increasing the crystallite size of the compound B contained in the solid electrolyte and suppressing the generation of hydrogen sulfide from the solid electrolyte. 50 From the viewpoint of enhancing the lithium ion conductivity of the solid electrolyte, it is preferable to adjust the degree of pulverization so that the volume cumulative particle size D of the solid electrolyte after wet pulverization is preferably 10 μm or less, more preferably 8.5 μm or less, and even more preferably 7.0 μm or less. 50 It is also preferable to adjust the degree of pulverization so that the crystallite size of the compound A contained in the solid electrolyte is controlled to increase the lithium ion conductivity of the solid electrolyte.

[0036] The solid electrolyte of the present invention thus obtained can be used, for example, as a material constituting a solid electrolyte layer or a material contained in an electrode mixture containing an active material. Specifically, it can be used as a positive electrode mixture constituting a positive electrode layer containing a positive electrode active material, or as a negative electrode mixture constituting a negative electrode layer containing a negative electrode active material. Therefore, the solid electrolyte of the present invention can be used in a battery having a solid electrolyte layer, that is, a so-called solid battery. More specifically, it can be used in a lithium solid battery. The lithium solid battery may be a primary battery or a secondary battery, and is preferably used in a lithium secondary battery. The term "solid battery" includes not only a solid battery that does not contain any liquid or gel material as an electrolyte, but also an embodiment that contains, for example, 50% by mass or less, 30% by mass or less, or 10% by mass or less of a liquid or gel material as an electrolyte.

[0037] The solid electrolyte layer in the solid battery can be produced by, for example, dropping a slurry containing the solid electrolyte of the present invention, a binder and a solvent onto a substrate and scraping it off with a doctor blade or the like, contacting the substrate with the slurry and then cutting it with an air knife, forming a coating film by screen printing or the like and then removing the solvent by heating and drying, or the like. Alternatively, the solid electrolyte layer can be produced by press-molding the powder of the solid electrolyte of the present invention and then appropriately processing it. The solid electrolyte layer may contain other solid electrolytes in addition to the solid electrolyte of the present invention. The thickness of the solid electrolyte layer in the present invention is typically preferably 5 μm or more and 300 μm or less, more preferably 10 μm or more and 100 μm or less.

[0038] From the viewpoint of enhancing lithium ion conductivity, the solid electrolyte layer containing the solid electrolyte of the present invention preferably has a porosity of, for example, 50% or less, more preferably 30% or less, and even more preferably 20% or less. The porosity of the solid electrolyte layer can be adjusted, for example, by the pressing pressure when the powdered solid electrolyte of the present invention is made into a compact. The pressing pressure is preferably, for example, 20 MPa or more. The porosity can be calculated from the true density and apparent density of the solid electrolyte layer, which are determined by, for example, a liquid phase method (Archimedes method), using the following relational expression. Porosity (%) = (true density - apparent density) ÷ true density × 100

[0039] It is also possible to use a mixture of the solid electrolyte of the present invention and another solid electrolyte as the solid electrolyte layer. When the solid electrolyte of the present invention is mixed with another solid electrolyte, the solid electrolyte of the present invention can be used in combination with, for example, any of amorphous (glass), glass ceramics, and crystalline materials. When the other solid electrolyte to be mixed with the solid electrolyte of the present invention is a sulfide solid electrolyte, specific examples of the sulfide solid electrolyte include Li2S-P2S5, Li4P2S6, Li7P3S, and Li2S-P2S5. 11 The solid electrolyte to be combined may be a non-sulfide, for example, an oxide-based solid electrolyte.

[0040] The solid-state battery has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer, and it is preferable that the solid electrolyte layer contains the solid electrolyte of the present invention. Examples of the shape of the solid-state battery include a laminate type, a cylindrical type, and a square type.

[0041] The positive electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a positive electrode active material. As the positive electrode active material, for example, a material used as a positive electrode active material for a lithium secondary battery can be appropriately used. As the positive electrode active material, for example, a spinel-type lithium transition metal compound, a lithium metal oxide having a layered structure, etc. can be mentioned. In addition to the positive electrode active material, the positive electrode mixture may contain other materials such as a conductive assistant.

[0042] The negative electrode mixture in the solid-state battery containing the solid electrolyte of the present invention contains a negative electrode active material. For example, a negative electrode mixture used as a negative electrode active material of a lithium secondary battery can be appropriately used as the negative electrode active material. For example, the negative electrode active material includes carbon materials such as lithium metal, artificial graphite, natural graphite, and non-graphitizable carbon (hard carbon), lithium titanate, titanium-niobium composite oxide, silicon, silicon compounds, tin, and tin compounds. In addition to the negative electrode active material, the negative electrode mixture may contain other materials such as a conductive assistant. EXAMPLES

[0043] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0044] Example 1 Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8Li2S powder, P2S5 powder, LiCl powder, and LiBr powder were weighed out so as to obtain a composition of the above. These powders were pulverized and mixed using a ball mill to obtain a mixed powder. The mixed powder was fired to obtain a fired product made of lithium ion conductive sulfide. The firing was carried out using a tubular electric furnace. During the firing, hydrogen sulfide gas with a purity of 100% was circulated through the electric furnace at 1.0 L / min. The firing temperature was set at 490°C, and firing was carried out for 4 hours. XRD measurement revealed that the fired product contained a crystal phase with an argyrodite-type crystal structure and LiCl. 0.5 Br 0.5 It was confirmed that the crystal phase was

[0045] The fired material was roughly crushed with a mortar and pestle, then crushed with a hammer crusher, and the crushed material was mixed with a solvent to form a slurry with a concentration of 10% by mass. This slurry was subjected to a bead mill device (zirconia beads with a diameter of 0.2 mm) and wet-pulverized. Toluene was used as the solvent for the slurry. After wet-pulverization, the slurry was subjected to solid-liquid separation, and the solid content was dried. The dried fired material was sieved with a sieve with an opening of 53 μm to obtain the desired solid electrolyte. In addition, other conditions such as the crushing time and energy were appropriately selected according to the desired solid electrolyte.

[0046] Example 2 In Example 1, the firing temperature, pulverizing device, slurry concentration, and media diameter were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0047] Example 3 The grinding device, slurry concentration, and media diameter in Example 1 were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0048] Comparative Example 1 In Example 1, the slurry concentration and media diameter were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0049] Comparative Example 2 In Example 1, the slurry concentration and media diameter were changed to the values ​​shown in the following Table 1. A solid electrolyte was obtained in the same manner as in Example 1 except for the above.

[0050] [Rating 1] The solid electrolytes obtained in the examples and comparative examples were subjected to Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8 Crystallite size of the crystalline phase and LiCl 0.5 Br 0.5 The crystallite size of the crystalline phase was determined. The volume cumulative particle size D 10 , D 50 and D. 95 The results are shown in Table 1 below.

[0051] [Measurement of crystallite size] A Rigaku SmartLab was used for the measurements. The optical system was focused, with a Johansson monochromator on the incident side and a D / teX Ultra 250 detector. A 5deg Soller slit was used for the incident and receiving parallel slits. A holder not exposed to air was used, the scanning axis was 2θ / θ, the scanning range was 20deg to 140deg, the step width was 0.01deg, and the scanning speed was set so that the maximum peak height was 10,000 counts or more. In addition, SRM660a (compound name: LaB6) manufactured by NIST (National Institute of Standards and Technology) was measured under the same conditions and used as a width standard. The analysis was performed using PDXL2 manufactured by Rigaku Corporation. The analysis procedure was as follows. First, identification was performed. The CIF file (Crystallographic Information File) described below was read and the substance was determined. The CIF file was obtained from ICSD (Inorganic Crystal Structure Database). The CIF file with ICSD Collection Code 418490 was used for compound A, and the CIF file with ICSD Collection Code 53818 was used for compound B. Next, intensity decomposition was performed using WPPF. For width correction, the width standard data file was selected. This file corresponds to the file in which the XRD data of SRM660a was measured, identified using LaB6, analyzed in the same manner as described below, and saved. The peak angle and width were corrected using an external standard sample. The "split-type Pearson VII function" was used as the model function for the peak shape. Next, from the "Basic" tab, "Refinement Parameter Settings" - "Method" was selected as "Intensity Decomposition". In addition, since the lattice constant changes depending on the combination of X (halogen atoms) in compound B, the initial value of the lattice constant of compound B was adjusted so that the XRD data and the calculated value were approximately the same. Next, refinement was performed. In the refinement, various parameters were adjusted until sufficient convergence was achieved. For example, the S value is 1.5 or less as a guideline. The analyzed crystallite size was obtained from "Display" - "Analysis Results".

[0052] [D 10 , D 50 and D. 95 Measurement of Using an automatic sample feeder for laser diffraction particle size distribution measurement equipment (Microtrac SDC manufactured by Microtrac-Bell Corporation), the sample (powder) was put into an organic solvent, and after irradiating it with 30W ultrasonic waves for 60 seconds at a flow rate of 50%, the particle size distribution was measured using a laser diffraction particle size distribution measurement equipment (MT3000II manufactured by Microtrac-Bell Corporation), and the D was calculated from the obtained volumetric particle size distribution chart. 10 , D 50 and D. 95 The organic solvent used was toluene.

[0053] [Measurement of BET specific surface area] The sample (powder) was heated in a vacuum at 120°C for 1 hour using a pretreatment device, "BELPREP-vacII" manufactured by Microtrack-Bell Co., Ltd. After that, the specific surface area was calculated by the BET (Brunauer-Emmett-Teller) method from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a specific surface area measuring device, "BELSORP-miniII" manufactured by Microtrack-Bell Co., Ltd.

[0054] [Evaluation 2] The amounts of hydrogen sulfide generated from the solid electrolytes obtained in the examples and comparative examples were measured by the method described below. The results are shown in Table 1 below. The solid electrolyte was weighed out in an amount of 50 mg in a glove box purged with sufficiently dried Ar gas (dew point: −60° C. or lower) and placed in a bag sealed with a laminate film. A 1500 cm container was placed in a thermohygrostat kept at room temperature (25°C) with a dew point of -30°C adjusted by mixing dry air and atmospheric air. 3 A glass separable flask was placed on the flask and kept until the inside of the separable flask became the same as the environment in the thermo-hygrostat. Next, the sealed bag containing the solid electrolyte was opened in the thermo-hygrostat, and the sample was quickly placed in the separable flask. The solid electrolyte was placed in the separable flask, and the hydrogen sulfide concentration was measured 60 minutes after the hydrogen sulfide was generated from immediately after the flask was sealed using a hydrogen sulfide sensor (GX-2009 manufactured by Riken Keiki). The volume of hydrogen sulfide was calculated from the hydrogen sulfide concentration after 60 minutes, and the amount of hydrogen sulfide generated after 60 minutes was determined.

[0055] [Rating 3] The lithium ion conductivity of the solid electrolytes obtained in the examples and comparative examples was measured by the method described below. The results are shown in Table 1 below. The solid electrolyte was uniaxially pressed in a glove box filled with sufficiently dried Ar gas (dew point -60°C or less). It was further pressed at 200 MPa using a cold isostatic press to produce a pellet with a diameter of 10 mm and a thickness of approximately 4 to 5 mm. Carbon paste was applied to both the top and bottom surfaces of the pellet as electrodes, and then heat treatment was performed at 180°C for 30 minutes to produce a sample for measuring ion conductivity. The lithium ion conductivity of the sample was measured using a Solartron 1255B manufactured by Toyo Corporation. The measurement was performed by an AC impedance method at a temperature of 25°C and a frequency of 0.1 Hz to 1 MHz.

[0056] [Table 1]

[0057] As is clear from the results shown in Table 1, the solid electrolytes obtained in the examples have lithium ion conductivity almost equivalent to that of the solid electrolytes of the comparative examples, while suppressing the generation of hydrogen sulfide. [Industrial Applicability]

[0058] According to the present invention, there is provided a solid electrolyte in which generation of hydrogen sulfide is suppressed.

Claims

1. It contains a crystal phase having an argyrodite type crystal structure, a P.S. b X c (X is at least one halogen element; a is a number of 3.0 or more and 6.0 or less; b is a number of 3.5 or more and 4.8 or less; and c is a number of 0.1 or more and 3.0 or less), LiX (wherein X has the same definition as above), A solid electrolyte, wherein the compound B has a crystallite size of 25 nm or more.

2. BET specific surface area is 14.0m 2 The solid electrolyte according to claim 1, wherein the molecular weight is 1 / g or less.

3. The solid electrolyte according to claim 1 or 2, wherein the crystallite size of the compound B is 70 nm or less.

4. 4. The solid electrolyte according to claim 1, which has a lithium ion conductivity of 4.0 mS / cm or more at 25° C.

5. The solid electrolyte according to claim 1 , wherein the compound A has a crystallite size of 50 nm or more.

6. The compound B is LiCl y B z 6. The solid electrolyte according to claim 1, wherein y and z are numbers that satisfy y+z=1.

7. The solid electrolyte according to claim 1, wherein the volume cumulative particle size D 50 at 50% of the cumulative volume measured by a laser diffraction scattering particle size distribution measurement method is 10.0 μm or less.

8. An electrode mixture comprising the solid electrolyte according to claim 1 and an active material.

9. A solid electrolyte layer comprising the solid electrolyte according to claim 1 .

10. A solid-state battery comprising the solid electrolyte according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Sulfide solid electrolyte

    US20190305371A1

  • Sulfide solid electrolyte

    WO2018047566A1